BEHAVIORAL AND BIO-PSYCHO-SOCIAL FACTORS IN CANCER SURVIVORSHIP - Antonino Di Meglio (Journal of Cancer Rehabilitation)
The incidence of cancer continues to rise, with over 26 million cancer survivors projected by 2040. As survival rates improve, attention must shift toward comprehensively addressing the needs of cancer survivors, not only including prevention of cancer recurrence, but also extending to surveillance and management of physical and psychosocial effects. However, current practices reveal suboptimal engagement in key survivorship services such as health promotion as well as in management of long-term treatment-related symptoms, which can signifcantly impact survivors' quality of life, and also affect medication adherence and, ultimately, clinical outcomes. Predisposition to clinically meaningful symptom burden after cancer and cancer-related frailty represents signifcant risks for a substantial portion of cancer survivors and such risks seem to be driven by multiple individual factors such as age, comorbidities, lifestyle, psycho-social traits, baseline symptom burden pre-treatment, and type of treatment